Identification of Flavonoid Compounds in Ethanol Extract of Chromolaena odorata L. Leaves Using Infrared Spectrophotometry - Suci Ramadani; Rahma Fatmawati; Clarissa Audhia Vhiona; Ifvia; Audi Ramadhani; Musda Lifah (JURNAL LENTERA ILMIAH KESEHATAN, 2026)
Flavonoids are an important group of secondary metabolites found in medicinal plants and possess various biological activities such as antioxidant, anti-inflammatory, and antibacterial properties. This study aims to identify and confirm the presence of flavonoid compounds in the ethanolic extract of Chromolaena odorata L. leaves using infrared spectrophotometry (FTIR) as a structural fingerprinting approach. Dried leaves were extracted by maceration using 90% ethanol, then the obtained extract was analyzed at a wavenumber range of 4000–400 cm⁻¹. FTIR results showed the presence of typical absorption of hydroxyl (–OH), carbonyl (C=O), aromatic double bonds (C=C), and ether (C–O–C) groups, which are the main characteristics of flavonoid structure. This spectral pattern is consistent with literature data and supporting phytochemical test results, thus confirming the role of FTIR as a qualitative confirmation tool and chemical fingerprint of flavonoid compounds in the ethanolic extract of C. odorata leaves. These findings strengthen the potential of this plant as a natural source of bioactive compounds for the development of standardized herbal medicines and further phytopharmaceutical research.